Batch and Column Studies for the Removal of Lead from Aqueous Solutions Using Activated Carbons from Viticultural Industry Wastes - A.C. Deiana; M.G. Gimenez; S. Rómoli; M.F. Sardella; K. Sapag (Adsorption Science & Technology)
Adsorption studies (kinetic, batch and dynamic assays) were carried out for lead removal from aqueous solutions using wastes from the wine industry. The adsorbents used were obtained from grape stalk and pomace # . These materials were carbonized, briquetted and activated with steam. Addition of a leaching step before activation lowered the high ash content of the materials. The products were characterized by elemental and proximate analysis, point of zero charge pH, specific surface area, pore-size distribution, Fourier transform infrared spectroscopy and surface acidic and basic groups. Considering the physicochemical and textural properties of the adsorbents, a comparative analysis of the results was made. These solids showed a marked basic character; therefore, the pH was a very important variable in adsorption tests, and thus it was necessary to maintain the pH in a favourable range. Batch equilibrium assays showed that the tested adsorbents had good adsorption capacities, better than the ones reported previously for similar materials. In dynamic tests, the removal of lead by both activated carbon briquettes was good and attributed to the coupling of adsorption and precipitation as a result of the increase in the pH values, which could not be controlled.